2016
DOI: 10.18632/oncotarget.9795
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of tobacco smoking and smoking-related DNA methylation with epigenetic age acceleration

Abstract: Recent studies have identified biomarkers of chronological age based on DNA methylation levels. Since active smoking contributes to a wide spectrum of aging-related diseases in adults, this study intended to examine whether active smoking exposure could accelerate the DNA methylation age in forms of age acceleration (AA, residuals of the DNA methylation age estimate regressed on chronological age). We obtained the DNA methylation profiles in whole blood samples by Illumina Infinium Human Methylation450 Beadchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 54 publications
(74 reference statements)
6
79
2
Order By: Relevance
“…Relationships of OS with telomere length and frailty have been shown by previous studies [45,46], while its link with the epigenetic clock remains unknown. Our previous work investigated the association of smoking-associated DNA methylation changes with the epigenetic clock and found that 66 out the same 151 smoking-related CpG sites were also related to age-related DNA methylation changes [47]. Interestingly, half of the 66 markers were also identified in the present study, including several frequently reported smoking-associated CpG sites: cg03329539 (2q37.1), cg05575921 (AHRR) and cg06126421 (6p21.33).…”
Section: Discussionsupporting
confidence: 56%
“…Relationships of OS with telomere length and frailty have been shown by previous studies [45,46], while its link with the epigenetic clock remains unknown. Our previous work investigated the association of smoking-associated DNA methylation changes with the epigenetic clock and found that 66 out the same 151 smoking-related CpG sites were also related to age-related DNA methylation changes [47]. Interestingly, half of the 66 markers were also identified in the present study, including several frequently reported smoking-associated CpG sites: cg03329539 (2q37.1), cg05575921 (AHRR) and cg06126421 (6p21.33).…”
Section: Discussionsupporting
confidence: 56%
“…46 In addition, Breitling et al showed that the epigenetic clock was correlated with the FI and further confirmed the robustness of this association across diverse domains of health deficits. 45 Our previous study on the relationship between smoking-induced DNA methylation and the epigenetic clock intriguingly found 7 out of the 9 now identified loci to be associated with the epigenetic clock as well, 47 including cg01127300, cg02657160 (CPOX), cg05673882 (POLK), cg07826859 (MYO1G), cg14753356, cg19589396 and cg23667432 (ALPP). The associations of smoking-related methylation with the FI and the epigenetic clock consequently share some pronounced commonalities, though the underlying causality certainly requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent subgroups were selected as the discovery and the validation panel for DNA methylation analyses as described previously. 47 Briefly, the discovery panel included 1,000 participants recruited consecutively at the start of the ESTHER study between July and October 2000. The validation panel included 548 participants randomly selected from participants recruited between October 2,000 and March 2001.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The DNAm age deviations from the chronological ages of the tumor‐free lung tissues might be explained by the possible presence of COPD or smoking habits 10. Among these, patients showing an age acceleration of more than 8 years (7 cases) smoked 63.1 pack‐years, while patients showing a deceleration of the DNAm age in the tumor‐free lungs (3 cases) smoked 23.3 pack‐years.…”
Section: Resultsmentioning
confidence: 99%